2005
DOI: 10.1016/s1607-551x(09)70275-x
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Subtalar Dislocation: A Case Report

Abstract: Anterior subtalar dislocations are extremely rare. To our knowledge, six cases have been reported in detail in the literature, but for only two of these was an anteroposterior view radiograph used to confirm the diagnosis. We report a case of anterior subtalar dislocation in which the posterior tibialis tendon was incarcerated in the talonavicular joint and that required an open reduction. We discuss the diagnosis, mechanism, and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Open reduction is seldom required and only indicated if there is interposition of tendon or bone fragments blocking the reduction. The case reported by Chuo et al 11 required open reduction because of posterior tibialis tendon incarceration. Theoretically, open reduction and internal fixation of the anterior calcaneal fracture was indicated in this case in order to restore the articular congruity of the calcaneocuboid joint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Open reduction is seldom required and only indicated if there is interposition of tendon or bone fragments blocking the reduction. The case reported by Chuo et al 11 required open reduction because of posterior tibialis tendon incarceration. Theoretically, open reduction and internal fixation of the anterior calcaneal fracture was indicated in this case in order to restore the articular congruity of the calcaneocuboid joint.…”
Section: Discussionmentioning
confidence: 99%
“…Tabib et al 10 reported that the dislocation followed a direct rear impact over the posterior aspect of heel after a fall injury. Chuo et al 11 reported that anterior subtalar dislocation occurred when the patient withdrew the trapped foot. In our case, the mechanism of injury was similar to that reported by Tabib et al .…”
Section: Discussionmentioning
confidence: 99%
“…18 Anterior subtalar dislocations are the least common and result from forces being transmitted through an excessively dorsiflexed foot. 19…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 6 out of 23 patients that were treated with open reduction and K-wires fixation had fair or poor final outcome. On the other hand, Kanda et al [16] and Chuo et al [17] reported good results and only mild ankle soreness after open reduction of the dislocation. Finally, Ganel et al [18] and Love et al [19] found that conservative and surgical treatment of closed subtalar dislocations were equal in terms of ankle and foot function.…”
Section: Discussionmentioning
confidence: 99%